Tafsir Iman Rahab dan Kedaulatan Allah dalam Yosua 2:1-12 Serta Relevansinya bagi Kesaksian Kristen di Masa Kini - Yohana Mallaga (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research is prompted by the unique narrative of Rahab, a Canaanite woman who occupies a critical theological position in Israel’s history of salvation despite her status as an outsider to the chosen people. The primary focus of this study is to explore the dimensions of Rahab’s faith and God’s sovereignty as recorded in Joshua 2:1-12. This study aims to analyze how the confession of faith from a marginalized individual aligns with God's sovereign plan and to determine the relevance of these values for contemporary Christian witness. The method employed is a qualitative approach utilizing library research and exegetical analysis of the text in Joshua 2:1-12. The findings indicate that Rahab's faith was not merely an act of self-preservation but a theological response to the formidable power of God that transcends ethnic boundaries and social status. God's sovereignty is proven capable of working through unexpected subjects to fulfill His divine purpose. The implications of this research assert that modern Christian witness must be inclusive and transformative, where the courage to declare God's truth amidst threatening situations constitutes a tangible form of living faith. The church is called to perceive God's sovereignty as the fundamental basis for mission and witness, unrestricted by social or cultural exclusivity.